2020
DOI: 10.3389/fimmu.2020.01712
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Zinc Supplementation on COVID-19 Pathogenesis

Abstract: During the current corona pandemic, new therapeutic options against this viral disease are urgently desired. Due to the rapid spread and immense number of affected individuals worldwide, cost-effective, globally available, and safe options with minimal side effects and simple application are extremely warranted. This review will therefore discuss the potential of zinc as preventive and therapeutic agent alone or in combination with other strategies, as zinc meets all the above described criteria. While a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
327
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(338 citation statements)
references
References 156 publications
(199 reference statements)
6
327
1
4
Order By: Relevance
“…Zinc supplements are traditionally prescribed for common cold ailments, usually caused by coronaviruses. Zinc supplements have been associated with a shortened duration of symptoms, reduced severity of illness, and more importantly with reduced morbidity and mortality in children (Wessels et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc supplements are traditionally prescribed for common cold ailments, usually caused by coronaviruses. Zinc supplements have been associated with a shortened duration of symptoms, reduced severity of illness, and more importantly with reduced morbidity and mortality in children (Wessels et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of patients develop ARSD accompanied by alveolar leak, leading to alveolar and interstitial edema with very limited oxygen exchange [49]. Zinc supplementation improves mucocilary clearance, strengthens epithelial integrity, reduces viral replication and lessens the risk of hyperinflammation, which includes an antioxidant effect while reducing lung damage and minimizing secondary infections [50].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency also impairs survival, proliferation, and maturation of monocytes, NK cells, T and B cells, phagocytosis by macrophages and neutrophils, as well as antibody responses to T cell-dependent antigens (181,182). It has been shown that correction of zinc deficiency boosts the defense-related immune system, and reduces mortality from infectious diseases and viral infections (222,232). From several controlled studies, it is clear that daily dietary supplementation of zinc for the elderly and children at high risk for zinc deficiency, is protective against infection and is associated with a decrease in mortality from infections in these populations (233)(234)(235)(236)(237).…”
Section: Minerals Zincmentioning
confidence: 99%